PENERAPAN STANDAR OPERASIONAL PROSEDUR PENGGUNAAN PERALATAN DALAM MENINGKATKAN PELAYANAN FOOD PRODUCTION DI HOLIDAY INN RESORT BARUNA BALI - Made Semara Yoga Dwi Darma Yoga; I Putu Gede Parma (Universitas Pendidikan Ganesha, 2026)
This study aims to analyze the implementation of Standard Operating Procedures (SOP) in the use of equipment in the Food Production department at Holiday Inn Resort Baruna Bali, as well as to evaluate its impact on service quality improvement. This is a descriptive qualitative study utilizing data collection techniques such as observation, interviews, and documentation. The findings show that the hotel has well-documented SOPs, such as the